2011
DOI: 10.1002/bip.22003
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic interactions in model peptide β‐hairpins: Ring current effects on proton chemical shifts

Abstract: Crystal structures of eight peptide β-hairpins in the sequence Boc-Leu-Phe-Val-Xxx-Yyy-Leu-Phe-Val-OMe revealed that the Phe(2) and Phe(7) aromatic rings are in close spacial proximity, with the centroid-centroid distance (R(cen)) of 4.4-5.4 Å between the two phenyl rings. Proton NMR spectra in chloroform and methanol solution reveal a significant upfield shift of the Phe(7) C(δ,δ') H(2) protons (6.65-7.04 ppm). Specific assignments of the aromatic protons have been carried out in the peptide Boc-Leu-Phe-Val-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 54 publications
2
50
0
1
Order By: Relevance
“…To overcome these problems, bortezomib analogues are targeted [18]. The peptide based vaccine Nano vaccine adjuvants, and aromatic peptides and beta amino acids are better tool of cancer treatment [19][20][21][22][23][24][25].…”
Section: Side Effects Of Bortezomibmentioning
confidence: 99%
“…To overcome these problems, bortezomib analogues are targeted [18]. The peptide based vaccine Nano vaccine adjuvants, and aromatic peptides and beta amino acids are better tool of cancer treatment [19][20][21][22][23][24][25].…”
Section: Side Effects Of Bortezomibmentioning
confidence: 99%
“…The second helical form, the C 14 helix, has the opposite directionality (C=O i ….. H-N i+4 ), which is unprecedented in α peptide sequences [3,4]. These reports sparked a flurry of activity on the conformational properties of β peptide oligomers.…”
Section: H-n I+3mentioning
confidence: 99%
“…These reports sparked a flurry of activity on the conformational properties of β peptide oligomers. An early study from Appavu et al [3][4][5][6][7], had demonstrated that unsubstituted β and γ amino acid residues can be incorporated into oligopeptide helices, without disturbing the overall helical fold [4].…”
Section: H-n I+3mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1985, Burley and Petsko observed, "that on an average about 60% of aromatic side chains in proteins are involved in aromatic pairs, 80% of which form networks of three or more interacting aromatic side chains [1][2][3][4][5][6]. Phenyl ring centroids are separated by a preferential distance of between 4.5 Å and 7 Å, and dihedral angles approaching 90° are most common"…”
Section: π…π Interactionmentioning
confidence: 99%